Pengetahuan Dan Sikap Personal Hygiene Ketika Menstruasi Pada Siswi Sekolah Menengah Kejuruan Bala Keselamatan Palu - Imelda Kantohe; Suwarty Nursahara Usman Putra; Fitri Arni Rasyidi; Saiful Ambodalle (AMMA : Jurnal Pengabdian Masyarakat, 2026)
According to the World Health Organization (WHO), an estimated 15 out of 20 female students will experience menstruation and vaginal discharge annually by 2025. This is based on a preliminary survey conducted in June 2025 at the Salvation Army Vocational High School in Palu. The study only involved 30 female students aged 15-18. Of the total, three students interviewed reported prolonged menstrual use, genital itching, menstrual pain, vaginal discharge, and irregular menstrual cycles. The purpose of this study was to determine the knowledge and attitudes regarding personal hygiene during menstruation among female students at the Salvation Army Vocational High School in Palu. This study employed a descriptive approach. The variables were students' knowledge and attitudes. Both primary and secondary data were used. The population was 30 female students at the Salvation Army Vocational High School in Palu. The sample size was the total population of 30. The results of this study indicate that of the 30 respondents, the highest knowledge was in the sufficient category (14 respondents (46.7%), poor (11 respondents (36.7%), and good (5 respondents (16.7%). Meanwhile, attitudes were poor (14 respondents (46.7%), and attitudes were adequate (16 respondents (53.3%). The conclusion of this study is that the knowledge and attitudes regarding personal hygiene during menstruation among female students were mostly adequate, and attitudes were mostly adequate. This study recommends that the Palu Salvation Army Vocational High School collaborate with health workers to provide information on personal hygiene during menstruation through reproductive health counseling. It is hoped that female students at the Palu Salvation Army Vocational High School will gain more insight into personal hygiene during menstruation.